Identification of the transcriptional targets of FOXP2, a gene linked to speech and language, in developing human brain. - Spiteri, E; Konopka, G; Coppola, G; Bomar, J; Oldham, M; Ou, J; Vernes, S; Fisher, S; Ren, B; Geschwind, D (2007)
Mutations in FOXP2, a member of the forkhead family of transcription factor genes, are the only known cause of developmental speech and language disorders in humans. To date, there are no known targets of human FOXP2 in the nervous system. The identification of FOXP2 targets in the developing human brain, therefore, provides a unique tool with which to explore the development of human language and speech. Here, we define FOXP2 targets in human basal ganglia (BG) and inferior frontal cortex (IFC) by use of chromatin immunoprecipitation followed by microarray analysis (ChIP-chip) and validate the functional regulation of targets in vitro. ChIP-chip identified 285 FOXP2 targets in fetal human brain; statistically significant overlap of targets in BG and IFC indicates a core set of 34 transcriptional targets of FOXP2. We identified targets specific to IFC or BG that were not observed in lung, suggesting important regional and tissue differences in FOXP2 activity. Many target genes are known to play critical roles in specific aspects of central nervous system patterning or development, such as neurite outgrowth, as well as plasticity. Subsets of the FOXP2 transcriptional targets are either under positive selection in humans or differentially expressed between human and chimpanzee brain. This is the first ChIP-chip study to use human brain tissue, making the FOXP2-target genes identified in these studies important to understanding the pathways regulating speech and language in the developing human brain. These data provide the first insight into the functional network of genes directly regulated by FOXP2 in human brain and by evolutionary comparisons, highlighting genes likely to be involved in the development of human higher-order cognitive processes.